DAMPAK PEMASANGAN DISTRIBUTED GENERATION TERHADAP RUGI-RUGI DAYA - Elias K. Bawan (Foristek, 2012)
The introduction of distributed generation (DG) onto distribution networks has a significant effect on power system. This effect cannot be characterized as detrimental or beneficial but is dependent on the allocation of DG on each distribution network section. Here the impact of DG on losses has been modeLED, facilitating a unique approach to the allocation of DG. This approach has been implemented and tested on sample sections of distribution network and results are presented showing the optimal allocation of DG which improves the efficiency of energy delivery on the distribution network. This paper aims to investigate the impact of distributed generation on distribution system losses. The main objective is to reduce the power losses based on location of DG and size of injection. Minimizing losses in the system is a delicate balance; one of the key areas is a balance between transmission losses andstorage losses. Distributed generation can save on transmission losses and must be carefully designed to ensure that storage and the losses associated are minimized. Distributed generation can be used in niche applications to assist distributed generation and help manage the variability of the transmission grid. Using application program ETAP 6.0 and the Manokwari electricity distribution system as case study, the results shows thatat certain location, the power injection of DG has decrease losses from 240,15 kW to 99,39 kW and more economic than without DG installation. The best location of interconnection is bus 77 from power grid and injection of 85% DG capacity.